2019
DOI: 10.1136/bmjopen-2018-024113
|View full text |Cite
|
Sign up to set email alerts
|

Five-year prognosis and impact of adolescent knee pain: a prospective population-based cohort study of 504 adolescents in Denmark

Abstract: ObjectivesInvestigate the prognosis of adolescent knee pain, and evaluate its impact on health, care-seeking and career choices 5 years later.DesignPre-registered, prospective cohort study.SettingPopulation-based cohort initiated in school setting.ParticipantsFrom a cohort of 2200 adolescents aged 15–19 years in 2011, 504 reported knee pain on at least a monthly basis, and were followed prospectively in this cohort study, together with 252 controls who did not have knee pain in 2011.Main outcome measuresOutcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 22 publications
1
64
0
Order By: Relevance
“…Musculoskeletal (MSK) pain can start early in life [1][2][3] and increases throughout adolescence [2,4,5]. Furthermore, knee pain [6,7], spinal pain [8] and MSK pain in general [2,9] have been shown to be recurrent conditions, and multi-site pain may exist already in adolescence [10][11][12]. Holden et al categorised adolescents into four classes describing their pain experience and demonstrated that multi-site pain was more common than pain in a single region [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Musculoskeletal (MSK) pain can start early in life [1][2][3] and increases throughout adolescence [2,4,5]. Furthermore, knee pain [6,7], spinal pain [8] and MSK pain in general [2,9] have been shown to be recurrent conditions, and multi-site pain may exist already in adolescence [10][11][12]. Holden et al categorised adolescents into four classes describing their pain experience and demonstrated that multi-site pain was more common than pain in a single region [10].…”
Section: Introductionmentioning
confidence: 99%
“…MSK pain in children may have a negative impact on sports participation [ 13 15 ], and physical activity in childhood is important for childhood and later health [ 16 ], highlighting the importance of optimizing MSK health. In addition, MSK problems in children have been linked to psychological distress [ 17 , 18 ], poor relations with peers [ 5 , 19 ], absence from school [ 13 ], puberty [ 20 , 21 ] and decreased quality of life [ 7 , 10 , 22 ]. To improve our understanding in this important area, and to learn when and how to intervene, we need more basic epidemiological knowledge about the occurrence and distribution of MSK problems in early life.…”
Section: Introductionmentioning
confidence: 99%
“…Further prospective research is needed to validate this finding, including studies with a clinical follow-up evaluation to determine if pain is indeed related to current OSD. However, we previously demonstrated in a follow-up study that very few adolescents without knee pain during adolescence developed knee pain at 5-year follow-up, 17 which would make it unlikely that the high proportion reporting knee pain at follow-up in the current study is unrelated to their history of OSD. These findings may have important implications for the evidence-based information that patients are given in the secondary care sector.…”
Section: Discussionmentioning
confidence: 62%
“…4,8,12,23 In fact, participants reported an OSD symptom duration of 90 months for those still experiencing knee pain, with 42.9% reporting daily knee pain. This risk of continued knee pain is slightly higher than that reported for patellofemoral pain (PFP) in adolescents, where a study by Rathleff et al 17 showed that 40.5% of adolescents still experienced knee pain after 5 years. We believe that this difference in the incidence of continued knee pain between adolescents with PFP and OSD may be due to the study design, as we had a shorter follow-up period and a more selective (hospital) population.…”
Section: Discussionmentioning
confidence: 74%
“…Non-traumatic knee complaints can be long-lasting, with an impact on health-related quality of life and physical activity [9][10][11] . In light of this, the management strategy initiated by the health care practitioner becomes critical to improve long term prognosis.…”
Section: Introductionmentioning
confidence: 99%